Stepwise tailward retreat of magnetic reconnection: THEMIS observations of an auroral substorm. Issue 5 (28th May 2016) - Ieda, A.; Nishimura, Y.; Miyashita, Y.; Angelopoulos, V.; Runov, A.; Nagai, T.; Frey, H. U.; Fairfield, D. H.; Slavin, J. A.; Vanhamäki, H.; Uchino, H.; Fujii, R.; et al.
Abstract: Auroral stepwise poleward expansions were clarified by investigating a multiple‐onset substorm that occurred on 27 February 2009. Five successive auroral brightenings were identified in all‐sky images, occurring at approximately 10 min intervals. The first brightening was a faint precursor. The second brightening had a wide longitude; thus, it represented the Akasofu substorm onset. Other brightenings expanded poleward; thus, they were interpreted to be auroral breakups. These breakups occurred stepwise; that is, later breakups were initiated at higher latitudes. Corresponding reconnection signatures were studied using Time History of Events and Macroscale Interactions during Substorms (THEMIS) satellite observations between 8 and 24 R E down the magnetotail. The Akasofu substorm onset was not accompanied by a clear reconnection signature in the tail. In contrast, the three subsequent auroral breakups occurred simultaneously (within a few minutes) with three successive fast flows at 24 R E ; thus, these were interpreted to be associated with impulsive reconnection episodes. These three fast flows consisted of a tailward flow and two subsequent earthward flows. The flow reversal at the second breakup indicated that a tailward retreat of the near‐Earth reconnection site occurred during the substorm expansion phase. In addition, the earthward flow at the third breakup was consistent with the classic tailward retreat near the end of the expansion phase; therefore, the tailward retreat is likely to have occurred in a stepwise manner. We interpreted the stepwise characteristics of the tailward retreat and poleward expansion to be potentially associated by a stepwise magnetic flux pileup. Key Points: Auroral stepwise poleward expansions were associated with reconnection stepwise tailward retreat This spatially stepwise association is consequence of magnetic flux pileup The stepwise association resolved objections to the Hones poleward leap concept